The complete Horowitz horror - Horowitz, Anthony, 1955- (Puffin Books, 2008)
Presents a collection of eighteen horror stories, set in England, that focus on everyday items that have sinister qualities, and includes computer games, a mysterious elevator, and a deadly cell phone.